Health promotion intervention to educate mothers of preschool children to promote wellness - Palavesam, Perianaayagi; Rajendran, Shankar Shanmugam; Venkatachalam, Gomathi Priya; Narayanasamy, Vanitha; Tamilselvi, Palani; Sheriff, Dhastagir Sultan (International Journal Of Community Medicine And Public Health, 2024)
Preschoolers are delicate individuals with higher rates of mortality and morbidity. Nowadays, the focus is to reduce mortality rates by focusing on risk factors, including preventable causes and elements that affect children's health. Creating an awareness among mothers in a particular community will help prevent and promote health among such children. Therefore, a study is designed to find out the effectiveness of focused intervention on health promotion among mothers of preschool children in selected urban area of Chennai. To validate the effectiveness of focused intervention a pre-test and posttest outcomes were measured to enable the wellness of preschool children. A quantitative research approach and pre-experimental design were used to gather data from 100 mothers of preschool children using convenience sampling technique. Self-structured knowledge questionnaires were used during pretest and post-test. After pretest, a focused intervention on health promotion among mothers of pre-school children was given. The outcome of the study was measured through a post-test. The data collected was analyzed, interpreted and the outcomes were reported. The average pre-test level of knowledge score of mothers was 8.22 and the average post-test knowledge score was 16.05, a significant difference (7.83). Mothers in nuclear family in the urban area having more than one child showed better outcome. Statistical significance was calculated using the chi-square test. The preliminary study’s findings support that focused intervention helps mothers to gain more knowledge that may help to maintain the health of their children. Such studies may be recommended to educate the mothers help reduce under five child mortality.